In TFIIH the Arch domain of XPD is mechanistically essential for transcription and DNA repair - Stefan Peissert (Nature Portfolio, 2020)
XPD is part of the TFIIH complex which plays major roles in transcription initiation and nucleotide excision repair (NER). Here the authors present a high-resolution crystal structure of the XPD-MAT1 interface and dissect the role of this interface in transcription and NER.